Great Powers and World Order : patterns and prospects - Kegley, Charles W.; Raymond, Gregory A. (California : CQ Press, an imprint of SAGE Publications, Inc., 2021)
"Great Powers and World Order encourages critical thinking about the nature of world order by presenting the historical information and theoretical concepts needed to make projections about the global future. Charles W. Kegley and Gregory Raymond ask students to compare retrospective cases and formulate their own hypotheses about not only the causes of war, but also the consequences of peace settlements. Historical case studies open a window to see what strategies for constructing world order were tried before, why one course of action was chosen over another, and how things turned out. By moving back and forth in each case study between history and theory, rather than treating them as separate topics, the authors hope to situate the assumptions, causal claims, and policy prescriptions of different schools of thought within the temporal domains in which they took root, giving the reader a better sense of why policy makers embraced a particular view of world order instead of an alternative vision"--
PART I: The violent origins of the contemporary World Order -- Great-power struggles for primacy in the modern era -- World War I and the Versailles Settlement -- World War II and the birth of the Liberal Order -- PART II: The fitful evolution of the contemporary World Order -- The Cold War and its consequences -- America's Unipolar moment -- Unraveling the Liberal Order -- PART III: Forging a New World Order -- The range of Great-Power choice in a time of system transformation -- Rethinking World Order.
Includes bibliographical references and index.
Keywords: International relations; International relations -- History; World politics; Globalization